1983
DOI: 10.1111/j.1432-1033.1983.tb07090.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Induction of the Synthesis of Phenylalanine Ammonia‐Lyase and of Chalcone Synthase in Elicitor‐Treated Plant Cells

Abstract: Changes in the rate of synthesis of phenylalanine ammonia-lyase and chalcone synthase, two characteristic enzymes of phenylpropanoid biosynthesis, have been investigated by direct immunoprecipitation of in vivo [35S]methionine-labelled enzyme subunits in elicitor-treated cells of dwarf French bean (Phaseolus vulgaris). Elicitor, heat-released from cell walls of Colletotrichum lindemuthianum, the causal agent of anthracnose disease of bean, causes marked but transient increases in the rates of synthesis of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…the causal agent of anthracnose disease, there is a marked increase in PAL activity 24 hr before the attainment of maximum phaseollin (XIII) and coumestrol (XV) levels which are spatially and temporally associated with necrotic lesions (685). In cell suspension cultures of the same plant, phaseollin accumulation can be induced by abiotic elicitors such as autoclaved ribonuclease A and by biotic elicitors present in culture filtrates and heat-released from a variety of fungi (52,115,170,188). The phytohormone composition of the culture medium is important in determining the magnitude of phaseollin accumulation in response to exogenous elicitor.…”
Section: Induction Of Enzymes Of Phytoalexin Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…the causal agent of anthracnose disease, there is a marked increase in PAL activity 24 hr before the attainment of maximum phaseollin (XIII) and coumestrol (XV) levels which are spatially and temporally associated with necrotic lesions (685). In cell suspension cultures of the same plant, phaseollin accumulation can be induced by abiotic elicitors such as autoclaved ribonuclease A and by biotic elicitors present in culture filtrates and heat-released from a variety of fungi (52,115,170,188). The phytohormone composition of the culture medium is important in determining the magnitude of phaseollin accumulation in response to exogenous elicitor.…”
Section: Induction Of Enzymes Of Phytoalexin Biosynthesismentioning
confidence: 99%
“…Therefore, the response has been further studied by measurement of changes in the rate of synthesis of PAL and CHS using in vivo pulselabeling with [35S]methionine coupled with specific, direct immunoprecipitation by antisera immunospecific for PAL and CHS, respective; this was followed by SDS-polyacrylamide gel electrophoresis of the immunoprecipitates and estimation of the incorporation of label into the enzyme subunits (170). Elicitor causes marked but transient increases in the rates of synthesis of both enzymes concomitant with the phase of rapid increase in enzyme activity at the onset of phaseollin accumulation.…”
Section: Molecular Mechanisms Regulating Levels Of Phytoalexin Biomentioning
confidence: 99%
“…PAL is encoded by a small gene family in plants with four members in Arabidopsis (Arabidopsis thaliana; PAL1-PAL4; Raes et al, 2003). A large number of studies have shown that PAL gene expression is responsive to a variety of environmental stimuli, including pathogen infection, wounding, nutrient depletion, UV irradiation, extreme temperatures, and other stress conditions (Lawton et al, 1983;Edwards et al, 1985;Liang et al, 1989aLiang et al, , 1989bDixon and Paiva, 1995). A number of studies have also employed molecular and genetic approaches to silence or disrupt the PAL genes for functional analysis of the gene family in plant growth, development, and responses to environmental stresses.…”
mentioning
confidence: 99%
“…Degradation of cAMP and cGMP is catalyzed by more or less specific 3 0 ,5 0 -cyclic nucleotide phosphodiesterases (EC 3.1.4.17) (Pietrowska-Borek et al, 2014a). (4) Plant cells respond to stress by intensifying production of various phenylpropanoic compounds (Lawton et al, 1983;Dixon and Paiva, 1995;Liu and McClure, 1995), such as flavonoids (Winkel-Shirley, 2001;Olsen et al, 2008), lignins (Moura et al, 2010), anthocyanins (Steyn et al, 2002;Bandurska et al, 2012) and salicylic acid (Hayat Abbreviations: PAL, phenylalanine:ammonia lyase; 4CL, 4-coumarate:coenzyme A ligase; C4H, cinnamate-4-hydroxylase; CHS, chalcone synthase; CCR, cinnamoylcoenzyme A:NADP oxidoreductase; ICS, isochorismate synthase; NH 2 -pA, adenosine 5 0 -phosphoramidate; F-pA, adenosine 5 0 -monophosphofluoride; SA, salicylic acid; HIT proteins, superfamily of proteins that contain histidine-triad sequence motif. Bandurska and Cie slak, 2013).…”
Section: Introductionmentioning
confidence: 99%